If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + -3 + -5x = -27 Reorder the terms: -3 + 1x + -5x = -27 Combine like terms: 1x + -5x = -4x -3 + -4x = -27 Solving -3 + -4x = -27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -4x = -27 + 3 Combine like terms: -3 + 3 = 0 0 + -4x = -27 + 3 -4x = -27 + 3 Combine like terms: -27 + 3 = -24 -4x = -24 Divide each side by '-4'. x = 6 Simplifying x = 6
| 6x-9x=11x | | 5+6x=4x+10 | | y=0.50x/111 | | 81r^2-5=59 | | 0=3W-8-35 | | 2.5(2)-0.2y=8.1 | | 25x^5-50x^4-x+2=0 | | y=0.50(111)+16 | | x^2-4x-14-x=0 | | 5=7(1)-y | | 7(x-1)+8=5x+2(1+x) | | 14xy-7x+15y-13xy= | | y=-5/6(2)+5 | | -a-3=-2a-3 | | -2/5x-99/10 | | 14y-9-8y-6= | | 6x-10(0)+2=0 | | y=0.50(50)+16 | | 6x-10(2)+2=0 | | 8d-23+d=42 | | y=0.50(100)+16 | | pq-7q+4p-9pq+2q= | | 4x^2+5y^2+16x+10y-79=0 | | 0.6-3.8=0.4 | | 9k+12s-14s+6k-3s= | | -3(t-4)+6t=7t-2 | | y=-0.80(55)+139 | | 2W+1=45 | | y=-0.80(45)+139 | | y=-0.80(35)+139 | | 4ab+12+3ab-15+ab= | | 2x^2+5x+2=135 |